2005
DOI: 10.1097/01.mbc.0000164433.43911.4f
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis with enoxaparin can produce a giant abdominal wall haematoma when associated with low doses of aspirin among elderly patients suffering cough attacks

Abstract: We report three patients aged 75-80 years observed in the Emergency Room with severe anaemia (requiring transfusion) due to a large abdominal wall haematoma while receiving standard prophylaxis against venous thromboembolism (40 mg/day enoxaparin for 6 days on average). All of them concomitantly received 100 mg/day aspirin because of previous ischaemic heart disease and presented similar clinical features: sudden onset of abdominal pain during a severe cough episode due to bronchial infection. A giant haematom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Nonsurgical trauma especially due to coughing or strenuous exercise is attributed to RSH formation in multiple cases. 6,7,16,17 One-third of our patients had coughing episodes. Coughing paroxysm can cause severe contractions of the abdominal muscles which can injure the epigastric vessels or the rectus muscle itself.…”
Section: Discussionmentioning
confidence: 82%
“…Nonsurgical trauma especially due to coughing or strenuous exercise is attributed to RSH formation in multiple cases. 6,7,16,17 One-third of our patients had coughing episodes. Coughing paroxysm can cause severe contractions of the abdominal muscles which can injure the epigastric vessels or the rectus muscle itself.…”
Section: Discussionmentioning
confidence: 82%
“…In such situations a high index of suspicion is necessary for early diagnosis and prompt anticoagulation for successful outcome 16. Prophylaxis for thrombosis is usually by enoxaparin 40 mg for 6 days on average 17. In this patient although prophylactic anticoagulation was given for a longer time, extensive PSMVT nevertheless had occurred.…”
Section: Discussionmentioning
confidence: 85%
“…It has been postulated that atrophy of the cutaneous and s.c. periumbilical tissues may predispose patients to the development of haematomas. 3 One published case study has shown, through aortic iliac and pelvic arteriography, that needle puncture of the inferior epigastric artery may have been a contributing factor to the occurrence of a rectus sheath haematoma in a patient receiving therapeutic doses of enoxaparin. 4 Cachectic and elderly patients with advanced periumbilical tissue atrophy are the primary cohort at risk, but clinicians should also be suspicious of males with central obesity.…”
mentioning
confidence: 99%